Evaluation of surra treatment strategies attacking horses and buffaloes in East Sumba District, Nusa Tenggara Timur Province of Indonesia (2010 – 2016) - Rita S. Dewi; April H. Wardhana; Retno D. Soejoedono; Sri Mulatsih (Indonesian Center for Animal Research and Development (ICARD), 2019)
Surra is a disease attacking livestock caused by a flagellated protozoan, Trypanosoma evansi. Indonesia archipelago is reported as an endemic country of the disease, except Sumba Island. However, Surra outbreak occurred in this Island in 2010 due to livestock movement from the neighbour island, Sumbawa. It generated high mortality in livestock, particularly in horses and buffaloes. The aim of the study was to evaluate the effectiveness of Surra treatment strategies in East Sumba District from 2010-2016 and to estimate the incidence of Surra in the next few months (forecast). The treatment strategy of Surra in East Sumba was divided into 2 (two) periods e.g. the first period in 2010-2011 using Isomethamedium as the single drug (period I) and the second period in 2012 - 2016 using a combination between diminazene aceturate as curative and isomethamedium as a prophylactic drug (period II). All data in the present study was obtained from the local livestock agency of East Sumba District from 2010 – 2016 when Surra outbreak occurred. The effectiveness of those two treatment strategies was compared using the proportion test. The results demonstrated that morbidity and mortality of horses and buffaloes were significantly greater in the period I (2010-2011) compared to period II (2012-2016). The treatment strategy in the period II was able to decrease the proportion of morbidity in horses and buffaloes for 1.44% and 0.66%, respectively. Likewise, the proportion of mortality in period II was also less than the period I from 3.79% to 1.30% for horses and from 2.80% to 0.55% for buffaloes. Based on forecasting study analysis using the control program projected with decomposition method for the next 12 months demonstrated that the treatment strategy in the period II could reduce the incidence and death of livestock by Surra. The treatment strategy using a combination between isometamedium and diminazene aceturate in East Sumba District might be more effective compared to using isometamedium alone.